Implementasi Metode Sobel pada Pengenalan Teknik Dasar Kendang Berbasis Augmented Reality - Yulyanto; Hendric Gunawan (Bulletin of Information Technology (BIT), 2023)
Kendang or Gendang is a music instrument that form of a long wood, bladdery inside and the hole is covered up with leather to be beaten. Kendang has been known by the Indonesian people since the seventh century and the Sundanese people (West Java) only knew about Kendang around 1584. Kendang has now been used as a means of musical arts education at various school levels, from elementary school up to university. In learning musical arts at school, students are required to know and to play all gamelan instruments. Due to limited tools, the learning process is only by conveying the material without being accompanied by the instrument technique. The impact, students only guess the sound produced by the Kendang without understanding theoretically how the technique to produce sound colors on the Kendang instrument is. This research aims to build an Augmented Reality application to introduce the basic techniques of playing kendang by displaying 3D Kendang animations. The method used to develop system is the RUP (Rational Unified Process) method. The RUP stages include inception, elaboration, construction and transition. UML diagrams are used at the elaboration stage to design the Augmented Reality application that will be created. The Sobel method is used at the construction stage. The result of this research is an Augmented Reality application that displays information about basic kendang techniques with 3D objects. Based on the result of UAT (User Acceptance Test), it shows that this application is accepted by users with a percentage value of 77.2%.